Sanitation Stories from Three Underserved Communities in Sri Lanka - Lakshman, Iresha M. (European Scientific Journal, ESJ, 2023)
The paper explores the sanitary experiences of people living in three low-income communities in Sri Lanka, namely Nawagampura, Salamulla and Mahaiyawa. Qualitative data gathered from 30 households through in-depth interviews were analysed thematically to develop and understanding of the nature and magnitude of the sanitation problems encountered by residents. Salamulla is a high-rise building where residents have been relocated from various shanty communities in Colombo. These complete houses have been given for free. In Nawagampura, similar shanty dwellers have been given two perches of land for free. Mahaiyawa is a shanty community occupied mainly by municipal council workers in Kandy. Vast majority of residents in all three sites do not have any legal documents to claim ownership to the house/ land. Overcrowding throughout several decades of occupation has resulted in various kinds of sanitation issues such as clogged canals and drainages, overflowing sewages, unclean public toilets, flooding, urinating in public, open defecation and ad hoc garbage disposal. Formal mechanisms to control these have failed due to unmanageability caused by magnitude of the offenses and laissez faire attitude among authorities and/or residents.